A Foregut Duplication Cyst of the Stomach in Association with a Gastrointestinal Stromal Tumor and a Leiomyoma: A Case Report. (21st December 2016) - Gagné, Andréanne; Sazonova, Olga; Marceau, Simon; Périgny, Martine; Joubert, Philippe
Abstract : Objectives . Duplication cysts are rare benign lesions usually arising in the gastrointestinal tract. We report a case of a 52-year-old woman with an incidental gastric mass found on computed tomography during a pregraft workup for a familial cardiomyopathy. Methods . The mass was completely excised by partial gastrectomy and gross examination revealed a cystic lesion containing two small solid nodules in its wall. Microscopic evaluation and immunohistochemistry study were performed to further characterize the cyst and the nodules. A comprehensive literature review of the NCBI database PubMed was also carried out. Results . While the cyst was diagnosed as a foregut duplication cyst, the solid nodules proved to be concomitant gastrointestinal stromal tumor (GIST) and leiomyoma. Both morphologic features and immunohistochemistry stains, including CD117, smooth muscle actin, and CD34 supported the diagnosis. Clinical course was benign and the patient had no clinical evidence of relapse ten months following the surgical procedure. The literature search did not reveal any other published case of a foregut duplication cyst presenting in combination with a GIST and a leiomyoma. Conclusions . To our knowledge, this is the first case of a composite lesion comprising a foregut duplication cyst of the stomach along with a leiomyoma and a GIST.